Study of the effect of neoadjuvant chemotherapy on the status of Her2/neu - Skálová, H; Dundr, P; Povýšil, C; Velenská, Z; Petruželka, L; Tvrdík, D (Folia biologica, 2011)
Her2/neu proto-oncogene amplification and protein over-expression is observed in 20-40 % of patients with breast cancer and plays a crucial role in invasive breast cancer and its treatment. A number of studies postulated the stability of Her2/neu gene expression, showing that in most patients the status of expression had not significantly changed after the neoadjuvant treatment. In the present study, we investigated samples from 20 patients with invasive breast carcinoma who had undergone neoadjuvant chemotherapy and subsequent surgery. In all cases, the expression level of Her2/neu was evaluated in both pre-therapeutically obtained tumour tissue by core needle biopsy and from specimens obtained during final surgery using immunohistochemistry. Fluorescence in situ hybridization and quantitative reverse transcription polymerase chain reaction methods were used for verifying the results obtained by immunohistochemistry. Her2/neu status determined by immunohistochemistry remained unchanged in 12 of 20 (60%) patients after neoadjuvant treatment. In six cases (30%) minor changes were observed after the treatment. However, in two cases (10%) we found altered Her2/neu expression from strongly positive in the pre-treatment biopsy to negative in the post-treatment surgery specimen. Moreover, this is the first report describing the changes in Her2/neu status at all protein, RNA and DNA levels by using immunohistochemistry, quantitative reverse transcription polymerase chain reaction and fluorescence in situ hybridization, respectively. By using variable methods we demonstrated possible new ways for Her2/neu detection and their dependability. Improvement in specific molecule detection can prevent the use of tailored targeted therapy in an untargeted manner.
Keywords: neoadjuvantní terapie; Humans; lidé středního věku; In Situ Hybridization, Fluorescence; intraduktální neinfiltrující karcinom; Female; polymerázová řetězová reakce s reverzní transkripcí; Carcinoma, Intraductal, Noninfiltrating; receptor erbB-2; lidé; Reverse Transcriptase Polymerase Chain Reaction; Immunohistochemistry; imunohistochemie; Breast Neoplasms; ženské pohlaví; hybridizace in situ fluorescenční; Middle Aged; Receptor, ErbB-2; Neoadjuvant Therapy; nádory prsu; Proto-Oncogene Mas; protoonkogen Mas